The impact of virtual map visual design and landmark description location on users’ wayfinding visual search performance and experience in intelligent shopping guide terminals - Xu, Le; Zhai, Weimin (Frontiers in Virtual Reality, 2025)
In large shopping malls, shoppers often require assistance with wayfinding. Intelligent shopping guide terminals are increasingly being used for this purpose, and their interface usability plays a crucial role in influencing both wayfinding visual search performance and the overall shopping experience. This study investigates the effects of map visual presentations and landmark description locations in virtual environments on users’ wayfinding visual search performance and subjective evaluations using intelligent shopping guide terminals. A 2x3 between subject design was employed to examine how different virtual map types (2D and 3D) and landmark description locations (on, within, or below the map) affect task performance and subjective evaluations. A total of 60 participants were selected via purposive sampling and asked to complete five wayfinding tasks. Task completion times were recorded, and data were collected using the System Usability Scale (SUS), a 7-point Likert scale for subjective evaluation, and semi-structured interviews. The key findings are as follows: (1) Landmark descriptions on or below the map led to better wayfinding visual search performance than those within the map; (2) Users demonstrated superior wayfinding visual search performance with 3D maps compared to 2D maps; (3) When landmarks were placed on or below the map, 3D maps outperformed 2D maps in task performance, attractiveness, and information clarity. However, the reverse was true when landmarks were placed within the map, (4) Landmark descriptions within the map generated higher physical demand, with no significant difference between descriptions on or below the map. (5) Overall, subjective evaluations and SUS scores indicated a clear preference for landmark descriptions placed on or below the map. These findings contribute to improving wayfinding visual search performance in shopping malls and offer valuable insights for enhancing user interface design in intelligent shopping guide terminals, ultimately leading to better user experiences.